COMPARATIVE BIOEFFICACY OF SOME NEW MOLECULES AGAINST JASSIDS AND WHITEFLY IN COTTON - R. K. KALYAN; D. P. SAINI; URMILA,; . P. JAMBHULKAR; BHISHEK PAREEK (The Bioscan, 2012)
Field studies were conducted during 2009 and 2010 to evaluate the bio-efficacy of some new molecules against jassids, Amrasca biguttula biguttula (Ishida) and whiteflies, Bemisia tabaci (Genn.) of cotton at Agricultural Research Station- Banswara (Rajasthan). Six molecules i.e. acephate 75 SP @ 500 a.i./ha, triazophos 40 EC @ 600 a.i./ha, fipronil 5 SC @ 40 a.i./ha, imidacloprid 70 WG @ 50 a.i./ha, spinosad 45 SC @ 75 a.i./ha and dimethoate 30 EC @ 300 a.i./ha were evaluated. Spinosad, imidacloprid, acephate and fipronil effectively control the population of jassids and whiteflies and gave significantly higher seed cotton yield over to untreated check and standard check. The highest avoidable losses (52.65%) were recorded in spinosad followed by imidacloprid (42.38%), acephate (31.47%), fipronil (28.23%) and dimethoate (28.12%).